The Effectiveness of a Training program based on the Inclusive Education approach to Remedy Reading Weakness for Female Basic Fifth Graders (Journal of the College of Basic Education, 2022)
This study aimed to reveal the effectiveness of a training program based on inclusive education approach to address the reading weakness among fifth grade female students, the researcher used the mixed research with a sequential interpretive design, where it relied on collecting quantitative data through the two tools (the observation card for reading skills, and the perceptual comprehension test), Then collect qualitative data to identify the effectiveness of the program from the point of view of a sample of (teachers, and parents), The sample of the study was (25) female students. Among the most important results is the determination of a list that includes the most important reading skills needed for the fifth grade, and The existence of effectiveness of the proposed program in treating reading comprehension, as the program achieved a great effect in treating reading comprehension. The researcher recommended actually strengthening the inclusive education approach by educational administrations, and strengthening the true partnership between all members of the school community.